2019
DOI: 10.1074/jbc.ra118.004614
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative actions of Tbc1d1 and AS160/Tbc1d4 in GLUT4-trafficking activities

Abstract: 2 The abbreviations used are: RabGAP, Rab GTPase-activating protein; AS160, Akt substrate of 160 kDa; CBD, calmodulin-binding domain; [Ca 2ϩ ] i , intracellular Ca 2ϩ concentrations; MSD, mean square displacement; PTB, phosphotyrosine-binding; QD, quantum dot; AMPK, AMP-activated protein kinase; EGFP, enhanced green fluorescent protein; ECFP, enhanced cyan fluorescent protein; NPE, nitrophenyl-EGTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Besides, a study indicates that PI3K/AKT pathway works as upstream signaling to stimulate the GLUT4 translocation to the cell surface in cardiomyocytes, thereby promoting glucose uptake (Yuan Y et al, 2019). During this procedure, GLUT4 translocation is mediated by AS160, which is activated through AKT phosphorylation (Hatakeyama H et al, 2019). Based on these discoveries, we propose that PI3K/AKT/AS160/GLUT4 signaling pathway plays an important role in the glucose uptake process during diabetes mellitus and its complications, like DN.…”
Section: Discussionmentioning
confidence: 92%
“…Besides, a study indicates that PI3K/AKT pathway works as upstream signaling to stimulate the GLUT4 translocation to the cell surface in cardiomyocytes, thereby promoting glucose uptake (Yuan Y et al, 2019). During this procedure, GLUT4 translocation is mediated by AS160, which is activated through AKT phosphorylation (Hatakeyama H et al, 2019). Based on these discoveries, we propose that PI3K/AKT/AS160/GLUT4 signaling pathway plays an important role in the glucose uptake process during diabetes mellitus and its complications, like DN.…”
Section: Discussionmentioning
confidence: 92%
“…These two insulin-dependent pathways (PI3K-Akt-AS160-Rab and Cbl-CAP-CrkII-C3G-TC10 pathways) induce an GDP-GTP switch and activate small G proteins, an important step in the trafficking of GLUT4 storage vesicles (GSV) to the PM [ 94 ]. Transport of GSV into the close vicinity with the PM is followed by the docking and fusion of the vesicles, with the support of SNARE complexes of proteins [ 93 , 95 ].…”
Section: Glut4 Translocationmentioning
confidence: 99%
“…Previously, we demonstrated that, in L6 myotubes, TBC1D4 deficiency increased the expression of CD36/SR-B2 and FABPpm, which, in turn, enhanced fatty acid influx into the muscle cells [ 13 ]. Importantly, AS160 (TBC1D4) has a less known structural homolog, TBC1D1, which has also been implicated in GLUT4 incorporation into the plasma membrane [ 16 ]. Given the above, we decided to add two additional experimental groups to our study, namely, the cells with the knocked down TBC1D1 and those with the simultaneous knockdown of both TBC1D1 and TBC1D4 .…”
Section: Introductionmentioning
confidence: 99%